Pelatihan 3M Pencegahan Penularan Covid-19 dengan Metode Bercerita untuk Anak Taman Kanan-Kanak Islam Terpadu (TKIT) Miftahussalam - Farida Noor Rohmah; Setya Putri Rahayu (Masyarakat Berdaya dan Inovasi, 2021)
Based on the observations at TKIT Miftahussalam, it was found that students were scheduled to attend school face-to-face once a week. Although limited in number, in fact, there are still some students who are negligent, for example, did not wear masks properly and did not keep their distance and were reluctant to frequently wash their hands with soap. Despite the school's repeated communication of health protocols, some students were still hesitant to put them into effect. The community service was themed "3M Practice Training for the Prevention of Covid-19 Transmission using the Storytelling Method for TKIT Miftahussalam Students" in response to these problems. The output of the results of this community service were the knowledge and awareness of TKIT Miftahussalam students about the importance of 3M, especially in the school environment. However, parental support and the home environment are still required.